(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
ACTIVAT3D copper is antimicrobial copper that can be rapidly deployed using SPEE3D technology. New algorithms allow SPEE3D printers to coat existing metal parts with copper which is more efficient than printing solid copper parts from scratch. Australian NATA accredited clinical trial speciality laboratory, 360Biolabs, tested the effect of ACTIVAT3D copper on live SARS-CoV-2 in their Physical Containment 3 (PC3) laboratory. The results showed that 96% of the virus is killed in two hours and 99.2% of the virus killed in 5 hours, while stainless steel showed no reduction in the same time frame. While the exact mechanism by which copper kills bacteria is still being studied, the laboratory data is compelling - on copper surfaces, bacteria and viruses die. When a microbe lands on a copper surface, the copper releases ions, which are electrically charged particles which react with moisture and oxygen to produce reactive oxygen. Copper ions and reactive oxygen rupture the outer membranes and destroy the whole cell, including the DNA or RNA inside. Because their DNA and RNA are destroyed, it also means a bacteria or virus can’t mutate and become resistant to the copper, or pass on genes (like for antibiotic resistance) to other microbes. The lab results show ACTIVAT3D copper surfaces behave much better than traditional stainless, which may offer a promising solution to a global problem as Stainless steel is currently the material typically used in hygiene environments. The technology can be used in any high traffic public area such as hospitals, schools, on ships or shopping centres. The Northern Territory Department of Trade, Business and Innovation was the first organisation to deploy antimicrobial ACTIVAT3D copper throughout their building to help fight the spread of COVID-19. SPEE3D was contracted to replace existing door handles within the building with ACTIVAT3D copper products. With these handles now installed, staff, and the community they interact with, are already experiencing the benefits of antimicrobial copper. The lab results have sparked global interest in this technology and SPEE3D receive daily enquiries from organisations looking for proactive ways to protect their communities.